Active RFID Wake-Up Receiver Subsystem for Freight Wagon Localization Devices - Łukasz Krzak; Cezary Worek (Sensors, 2025)
This paper presents the concept, design, and performance analysis of an active radio wake-up and radio identification subsystem as part of an advanced localization device intended to operate within a large-scale freight wagon localization system. The system provides an efficient and cost-effective way to localize freight carriages, which, in the majority of cases, are currently not tracked. The localization device is battery-powered and uses an ultra-low-power radio interface for detecting wake-on-radio signals from nearby operator devices. The same interface is also used for communication within an ad-hoc wireless mesh network, which allows the localization devices to select the best device to send out localization information from the whole cluster through a cellular connection in order to minimize overall battery energy usage. The article presents the overall system architecture construction of the radio interface, including the wake-up subsystem, as well as the results of performance measurements.